Roles of the AMPA receptor subunit GluA1 but not GluA2 in synaptic potentiation and activation of ERK in the anterior cingulate cortex - Sprengel Rolf; Seeburg Peter H; Xu Hui; Wu Long-Jun; Ulzhöfer Bettina; Zhao Ming-Gao; Toyoda Hiroki; Kuner Rohini; Zhuo Min (SAGE Publishing, 2009)
Abstract Cortical areas including the anterior cingulate cortex (ACC) are important for pain and pleasure. Recent studies using genetic and physiological approaches have demonstrated that the investigation of basic mechanism for long-term potentiation (LTP) in the ACC may reveal key cellular and molecular mechanisms for chronic pain in the cortex. Glutamate N-methyl D-aspartate (NMDA) receptors in the ACC are critical for the induction of LTP, including both NR2A and NR2B subunits. However, cellular and molecular mechanisms for the expression of ACC LTP have been less investigated. Here, we report that the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunit, GluA1 but not GluA2 contributes to LTP in the ACC using genetic manipulated mice lacking GluA1 or GluA2 gene. Furthermore, GluA1 knockout mice showed decreased extracellular signal-regulated kinase (ERK) phosphorylation in the ACC in inflammatory pain models in vivo. Our results demonstrate that AMPA receptor subunit GluA1 is a key mechanism for the expression of ACC LTP and inflammation-induced long-term plastic changes in the ACC.